Bridging the Gap: A Systematic Review of Policy and Practice in Technology-Enhanced Learning in Secondary and Higher Education - Malizal, Zelynda Zeinab; Rizqi, Putri Umrotur (Sinergi International Journal of Education, 2023)
Integrating educational technology has transformed learning methodologies, enhancing student engagement and academic performance. This study investigates the role of digital literacy, interactive media, and problem-based learning in improving education. A systematic literature review was conducted using Google Scholar, Scopus, and Web of Science to analyze trends and challenges in technology-based education. The findings reveal that interactive learning environments significantly enhance critical thinking, student motivation, and content retention. However, systemic barriers such as unequal access to digital resources, inadequate teacher training, and policy limitations hinder effective implementation. Comparative analysis with international studies highlights the need for tailored approaches in different educational contexts. The discussion underscores the necessity for policy reforms, increased investment in digital infrastructure, and collaborative efforts between educators and technology providers. This study concludes that while educational technology offers immense potential, overcoming systemic challenges is crucial for maximizing its benefits. Future research should focus on the long-term effects of technology in education and its impact on student development across diverse learning environments.